Trade Facilitation and Africa’s Manufactured Goods Export - Akinkugbe, Oluyele (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
This paper examines the issues of why; even in the light of reductions in tariff and non-tariff barriers in many African countries in recent times, government policies, including restrictive trade and poor customs regulations and administration––issues of trade facilitation––still continue to discourage exporting. A panel data analysis was undertaken to consider a variety of indicators of trade facilitation and test their relative efficacy on trade flows in a multi-country framework. Time series data on 20 selected African countries were pooled in this regard. Our conclusions are that policy-regime improvements and conscious efforts at removing all forms of constraints to the free flow of goods– –reducing trade and customs regulations––from current levels, could have a significant impact on trade expansion in Africa.